Sleep in hospitalized children and adolescents: A scoping review. (October 2021) - Hybschmann, Jane; Topperzer, Martha K.; Gjærde, Line K.; Born, Peter; Mathiasen, René; Sehested, Astrid M.; Jennum, Poul J.; Sørensen, Jette L.
Summary: Hospitalized children and adolescents are at risk of short sleep and subsequent adverse health effects, but little is known about actual sleep duration, the factors that cause sleep disturbances in an inpatient pediatric setting, and what has been done to promote sleep in this population. The aim of this review was to systematically identify, categorize, and synthesize the literature on sleep in children and adolescents in an inpatient setting. We searched five electronic databases (PubMed, CENTRAL, CINAHL, PsycINFO, and Scopus) and of the 3770 references identified, 28 were eligible for inclusion. From studies reporting age-specific sleep durations, we found that four out of nineteen fell within the National Sleep Foundations recommendations for age-specific sleep durations. Reported causes of sleep disturbances were primarily related to modifiable, external factors, e.g., nursing care activities and noise from equipment and other patients. Sleep-promoting interventions seemed acceptable to patients, parents, and healthcare professionals. However, the literature in this area is heterogeneous regarding methodology, reporting, and population characteristics. Our findings underline the importance of prioritizing and optimizing sleep in hospitalized pediatric patients and highlight the need for standardization in the planning and reporting of studies within this field.